Analysis of residence patterns of Sperm whales (Physeter macrocephalus) in Azores Islands using opportunistic data - Oliveira, Beatriz (2013)
Sperm whales are one of the main targets of the whale watching operations on the Azores archipelago. Observations made from commercial platforms, many of which collected in the context of the MONICET project, provide a low-cost and large dataset from which to study this species. The aim of this study is to analyze the residence patterns of sperm whales in selected areas of the Azores archipelago. Data was collected from 2005 to 2012 and comprises two different geographic areas (the islands of Pico Island and of Sao Miguel). A total of 1133 photographs were obtained from different opportunistic platforms and pooled together in a common database. Animals were individually identified using photo-identification methods. Residence times were analyzed by plotting lagged identification rates against time lag and fitting a series of population models implemented in Socprog 2.4 program. Selection of the best fitting models was determined using the lowest Quasi Akaike Information Criterion (QAIC) value. A total of 391 animals were identified in Pico (resighting rate of 27%) and 199 animals were identified in Sao Miguel (resighting rate of 23%). Some of the individuals have been resighted in both islands suggesting the existence of movements between islands. Preliminary results show that sperm whales spend 14.13 days around Sao Miguel Island and 4.12 days around Pico Island. Expected results will elucidate if there is a meaningful population exchange between islands.